Steroid hormone regulation of EMP2 expression and localization in the endometrium - Williams Carmen J; Gordon Lynn K; Rao Rajiv G; Morales Shawn A; Mainigi Monica; Wadehra Madhuri; Braun Jonathan (BMC, 2008)
Abstract Background The tetraspan protein epithelial membrane protein-2 (EMP2), which mediates surface display of diverse proteins, is required for endometrial competence in blastocyst implantation, and is uniquely correlated with poor survival from endometrial adenocarcinoma tumors. Because EMP2 is differentially expressed in the various stages of the murine and human estrous cycle, we tested the hypothesis that the steroid hormones progesterone and estrogen influence EMP2 expression and localization. Methods Frozen human proliferative and secretory endometrium were collected and analyzed for EMP2 expression using SDS-PAGE/Western blot analysis. The response of EMP2 to progesterone and estradiol was determined using a combination of real-time PCR, SDS-PAGE/Western blot analysis, and confocal immunofluorescence in the human endometrial carcinoma cell line RL95-2. To confirm the in vitro results, ovariectomized mice were treated with progesterone or estradiol, and EMP2 expression was analyzed using immunohistochemistry. Results Within normal human endometrium, EMP2 expression is upregulated in the secretory phase relative to the proliferative phase. To understand the role of steroid hormones on EMP2 expression, we utilized RL95-2 cells, which express both estrogen and progesterone receptors. In RL95-2 cells, both estradiol and progesterone induced EMP2 mRNA expression, but only progesterone induced EMP2 protein expression. To compare steroid hormone regulation of EMP2 between humans and mice, we analyzed EMP2 expression in ovarectomized mice. Similar to results observed in humans, progesterone upregulated endometrial EMP2 expression and induced EMP2 translocation to the plasma membrane. Estradiol did not promote translocation to the cell surface, but moderately induced EMP2 expression in cytoplasmic compartments in vivo. Conclusion These findings suggest that targeting of EMP2 to specific locations under the influence of these steroid hormones may be important for integrating the molecular responses required for implantation competence.